The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fbioe.2023.1131053
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted cassava pulp hydrolysis as food waste biorefinery for biodegradable polyhydroxybutyrate production

Abstract: Cassava pulp is one of the most abundant agricultural residues that can cause serious disposal problems. This study aimed to apply a biorefinery approach by examining the feasibility of microwave-assisted cassava pulp hydrolysis to attain sustainable management and efficient use of natural resources. Four factors, namely, the liquid-to-solid ratio (20 mL/g, 10 mL/g, 7.5 mL/g, and 5 mL/g), types of acids (H2SO4 and H3PO4), watt power (600 W, 700 W, and 800 W) and time (3, 5 and 8 min), were carefully investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Another green extraction in the form of microwave-assisted hydrolysis on cassava pulp biomass waste for bioplastic (PHB) was performed by another research team ( Prasetsilp et al, 2023 ). Such a technique offers better radiation input and time and temperature control than alkaline and enzymatic treatments.…”
Section: Green Extraction On Bioreactor-produced Bioplasticmentioning
confidence: 99%
“…Another green extraction in the form of microwave-assisted hydrolysis on cassava pulp biomass waste for bioplastic (PHB) was performed by another research team ( Prasetsilp et al, 2023 ). Such a technique offers better radiation input and time and temperature control than alkaline and enzymatic treatments.…”
Section: Green Extraction On Bioreactor-produced Bioplasticmentioning
confidence: 99%
“…According to Matsui et al ( 2004), the chemical composition of CP varies between 40-60% starch, 15-50% cellulose, and other components, such as proteins and fat. Moreover, the compositions of the CP varied with changes in the species, cultivation location, cultivation conditions, harvest period and production process [28].…”
Section: Cassava Pulp Compositionsmentioning
confidence: 99%
“…As a result, it starts to spoil right away and gives off an offensive odor and pollutes ground water. According to previous reports, cassava pulp contains 40%-80% starch and 20%-40% fibers depending on the starch milling technology, plant variety and other environmental factors [28][29][30]. Sinsukudomchai et al studied a green composite made of PHB and long-chain fatty acid esterified microcrystalline cellulose from pineapple leaf (esterified PALF-MCC laurate).…”
Section: Introductionmentioning
confidence: 99%
“…These inhibitors must be controlled and reduced to a minimum level during the process to achieve the sustainable production of precursor fermentable sugar molecules for ethanol production. The factors responsible for inhibitor production include reaction temperature, acid concentration, autoclave time, and solid biomass concentration [12]. Studies have shown that pretreatment of solid biomass with high acid and temperature generates higher concentrations of degradation products like furfural and HMF, with an improved chance of fermentable sugar yield from the process [13].…”
Section: Introductionmentioning
confidence: 99%